Effect of the leachate head on the key pollutant indicator in a municipal solid waste landfill barrier system. (1st June 2019) - Shu, Shi; Zhu, Wei; Xu, Haoqing; Wang, Shengwei; Fan, Xihui; Wu, Silin; Shi, Jianyong; Song, Jie
Abstract: In previous studies of municipal solid waste (MSW) landfill barrier systems, chemical oxygen demand has been found to be the key pollutant indicator when estimating the breakthrough time for. However, the leachate head in a municipal solid waste landfill can be very high (>10 m in some Chinese landfills). The key pollutant indicator could be different at different leachate heads. The leachate head will continuously change during the use of a landfill. Different pollutants have different transport characteristics in the leachate, so it is necessary to determine whether changes in the leachate head change the key pollutant indicator for identifying breakthrough in a landfill barrier system. In this study, numerical models were used to investigate transport of common leachate pollutants through four typical landfill barrier systems with different leachate heads. Chemical oxygen demand reached the breakthrough threshold before the other pollutants, irrespective of (1) the leachate head and (2) changes in the leachate head. It was therefore clear that the leachate head did not affect the selection of the key pollutant indicator for identifying breakthrough in a landfill barrier system. Graphical abstract: Image 1 Highlights: The influence of the leachate head on the breakthrough time of the landfill liners was investigated. The effect of the leachate head on the pollutant indicator selection for breakthrough was studied. An effective method was established to provide a reference for design and management of landfills.